The effect of fast-food service quality and customer satisfaction on customer loyalty mediated by trust at McDonald’s restaurants in Surabaya - Layunwira, Sisilia; Andajani, Erna (Southeast Asian Journal of Service Management, 2024)
This study aims to determine and analyze the effect of fast-food service quality and customer satisfaction on customer loyalty mediated by trust. The object taken is the McDonald's fast-food industry in Surabaya. This study uses primary data sources by distributing questionnaires online. Data processing in this study using SPSS 20 and SmartPLS 3.0 software. Data processing using SPSS 20 software is to test the validity and reliability using 30 initial respondents. Further testing uses 150 respondents using SmartPLS 3.0 software using the SEM (Structural Equation Modeling) method. In this study, a sample of 210 respondents who were McDonald's customers in Surabaya were used. The results showed that Fast Food Service Quality has a significant effect on Customer Satisfaction, Customer Satisfaction has a positive and significant effect on Customer Loyalty, Customer Satisfaction has a positive and significant effect on customer loyalty with the mediating role of trust.